IMPLEMENTATION OF FLIPBOOK LEARNING MEDIA TO IMPROVE MOTIVATION AND ACHIEVEMENT IN BIOLOGY LEARNING IN CLASS XII MIPA2 STUDENTS OF SMAN 1 KUTA SELATAN - Made Eka Adnyana (Lembaga Pengembangan Pembelajaran Penelitian dan Pengabdian Masyarakat Universitas PGRI Mahadewa Indonesia, 2023)
This study aims to increase motivation and achievement in learning biology in class XII MIPA2 SMA Negeri 1 Kuta Selatan through the implementation of flipbook learning media. This research was conducted from 26 July 2022 to 8 October 2022, with research subjects being class XII MIPA2. The object of this research is the motivation and achievement in studying biology. Student motivation data was collected through questionnaires and learning achievement data collected through learning achievement tests arranged in the form of objective tests. The data that has been collected, then analyzed descriptively. The results of this study indicate that there is an increase in student motivation and achievement through the implementation of flipbook learning media. good category. The average student achievement in the first cycle was 65.57 in the sufficient category and 51.43% student completeness, while in the second cycle the average student achievement was 79.71 in the good category and 88.57% student completeness.